2001
DOI: 10.1111/j.1547-5069.2001.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

A Quality of Health Outcomes Model for Guiding Obstetrical Practice

Abstract: Research findings indicate that interventions such as cesarean delivery and epidural analgesia may result in several significant quality of health outcomes for women that should receive increased attention. Uses of this model for shaping best practices among physicians and nurses and for setting directions for priorities in future interdisciplinary research and health policy are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The QHOM posits reciprocal interactions among the four constructs (system, intervention, outcome, and client), thus serving as a useful conceptual guide for health care systems researchers. Several investigators have used the QHOM model in acute and community care to organize their choice of variables among the four constructs and to build evidence regarding the quality of health care (Mayberry & Gennarro, 2001;Radwin & Fawcett, 2002;Sin, Belza, LoGerfo, & Cunningham, 2005). In this study, system variables included hospital characteristics such as teaching status, ownership status, size, location, and nurse staffing levels; intervention variables were defined as utilization of patient safety practices; outcomes, or patient safety indicators, were defined by the Agency for Healthcare Research and Quality (AHRQ, 2007); and client characteristics were defined as riskadjusted variables including diagnosis, age, and gender.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The QHOM posits reciprocal interactions among the four constructs (system, intervention, outcome, and client), thus serving as a useful conceptual guide for health care systems researchers. Several investigators have used the QHOM model in acute and community care to organize their choice of variables among the four constructs and to build evidence regarding the quality of health care (Mayberry & Gennarro, 2001;Radwin & Fawcett, 2002;Sin, Belza, LoGerfo, & Cunningham, 2005). In this study, system variables included hospital characteristics such as teaching status, ownership status, size, location, and nurse staffing levels; intervention variables were defined as utilization of patient safety practices; outcomes, or patient safety indicators, were defined by the Agency for Healthcare Research and Quality (AHRQ, 2007); and client characteristics were defined as riskadjusted variables including diagnosis, age, and gender.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The QHOM has been used by a variety of researchers. Mayberry and Gennaro, 19 for example, applied the model to a review of second‐stage labor in obstetric care and suggested that specific interventions, such as cesarean delivery and epidural analgesia, will differ in their outcomes, depending on system (eg, skill mix, policies) and patient characteristics. Radwin and Fawcett 20 retrospectively used the model to guide their work in identifying aspects of patient characteristics, interventions, and systems of care for oncology patients.…”
Section: Introductionmentioning
confidence: 99%
“…One of the innovations of this study is an empirical measure of the quality of nurses’ work environments that permits a direct test of the QHOM. A literature review shows that the QHOM is useful to theoretically guide studies that evaluate system interventions such as nurse staffing, improved patient care, and outcomes (Borglund, 2008; Gerolamo, 2006; Mayberry & Gennaro, 2001; Newhouse, Johantgen, Pronovost, & Johnson, 2005; Vahey et al, 2004). Nursing can be thought of as a healthcare organization's surveillance system for the early detection of adverse events (Clarke & Aiken, 2003).…”
mentioning
confidence: 99%